Peppa Pig. Peppa's Christmas [videorecording (DVD)]. (Entertainment One, 2014)
Peppa Pig follows the hilarious adventures of Peppa, a loveable little piggy, her family, and all of her animal friends, including Suzy Sheep, Pedro Pony, Danny Dog and more. Peppa loves playing games and making new friends, but her absolute favorite thing is jumping up and down in muddy puddles!